1982
DOI: 10.1111/j.1939-165x.1982.tb00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Equine Thoracic Fluid

Abstract: Eighteen clinically normal horses were used to study the characteristics of normal thoracic fluid. Thoracic fluid was obtained from each horse and was found to be similar to equine abdominal fluid. Total leukocytes averaged 3994/ul, total protein 1.8 g/dl, and specific gravity 1.015. Analysis of thoracic fluid from 16 horses with clinical signs of thoracic disease showed abnormalities in every case. Thoracic fluid analysis alone determined a specific diagnosis in 50% of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…In cases of pleuritis this is an exudate with a high protein content (up to 7.8 g/lW ml) and white blood cell count (up to 350 x 10g/litre) in which neutrophils predominate (Smith 1977). Pleural fluids from horses with thoracic lymphosarcoma are modified transudates and generally have lower protein levels and a predominance of lymphoid cells, many of which are bizarre and have mitotic figures (Schalm 1981;Wagner and Bennett 1982). Other causes of pleural effusions in horses include mesothelioma (Kramer.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of pleuritis this is an exudate with a high protein content (up to 7.8 g/lW ml) and white blood cell count (up to 350 x 10g/litre) in which neutrophils predominate (Smith 1977). Pleural fluids from horses with thoracic lymphosarcoma are modified transudates and generally have lower protein levels and a predominance of lymphoid cells, many of which are bizarre and have mitotic figures (Schalm 1981;Wagner and Bennett 1982). Other causes of pleural effusions in horses include mesothelioma (Kramer.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors, however, did not find any eosinophils in a series of 20 normal and 20 abnormal horses (Swanwick and Wilkinson 1976). In a cytology study of thoracic fluid recovered from 18 normal horses, only one had eosinophils, 0.064 x 109A (Wagner and Bennett 1982). Eosinophils are known to attach to nematodes and release several substances, one of which is major basic protein, a substance capable of damaging the nematodes' wall (Slausson and Cooper 1990).…”
Section: Eosinophilsmentioning
confidence: 99%
“…It normally contains 2 to 3 ml of fluid in dogs and cats, with low cell numbers (<500 cells/ μl) and protein content (<1.5 g/dl). Regarding horses, it has been reported that 2 to 8mL of thoracic fluid could be aspirated by 17 out of 18 clinically normal horses, however multiple attempts were made in order to obtain the fluid (Wagner and Bennett, 1982). Its production depends mainly on the colloid osmotic pressure and the hydrostatic pressure within the capillary and lymphatic beds which means that lymphatics gather the surplus left after fluid filtration by the capillaries.…”
Section: Introductionmentioning
confidence: 99%